2016
DOI: 10.1111/coa.12597
|View full text |Cite
|
Sign up to set email alerts
|

Refining the head and neck cancer referral guidelines: a two‐centre analysis of 4715 referrals

Abstract: This study presents a significantly refined version of referral guidelines which demonstrate greater diagnostic efficacy than the current NICE guidelines. We recommend that further iterative refinements of referral criteria be considered when referring patients with suspected HNC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…Assuming dentists do not refer all these patients on to the two-week wait pathway this could reduce the burden placed on the service. Also in support of this approach, Tikka et al 4 concluded that red and white patches are a poor predictor of cancer with a predictive value of 4% (although this exceeds the >3% target set by NICE guidance), but that oral swelling is an important indicator of potential cancer. However, NG12 guidance may expose patients to increased risk of delayed referral because there is no clear referral pathway between doctors and dentists for suspected cancer.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Assuming dentists do not refer all these patients on to the two-week wait pathway this could reduce the burden placed on the service. Also in support of this approach, Tikka et al 4 concluded that red and white patches are a poor predictor of cancer with a predictive value of 4% (although this exceeds the >3% target set by NICE guidance), but that oral swelling is an important indicator of potential cancer. However, NG12 guidance may expose patients to increased risk of delayed referral because there is no clear referral pathway between doctors and dentists for suspected cancer.…”
Section: Discussionmentioning
confidence: 97%
“…4 A referral from a dentist with a lump on the lip, or in the oral cavity, consistent with cancer, or a patch that is either red, or red and white, that is consistent with oral cancer 6 1.8. 5 An unexplained thyroid lump 0 by pain, or bleeding or swelling, or both, for a referral for suspected cancer).…”
Section: 83mentioning
confidence: 99%
“…Compared to other international centers, the rate of malignant cases among individuals referred to our institution is high (63.9% overall, considering cases highly suspect, and 78.7%, considering cases only in group B). British studies with patients with complaints related to UADT diseases showed variable rate between 8 and 15% of malignancy [19][20][21][22] . It is important to note that in Brazil and in the United Kingdom the referral criteria of the patient with suspicion of upper airway digestive tract cancer to the specialist are very similar and should be sent to the oncology centers of SUS those patients with suspected or confirmed malignant neoplasia.…”
Section: /11mentioning
confidence: 99%
“…In 2016, our group used information from a cohort of 4715 patients referred in for suspected HNC to generate a 13-symptom inventory which, when combined with age, could generate a personalized risk of cancer with a high diagnostic efficacy (area under the curve [AUC] 0.77). 10 Sensitivity analysis identified the 8% risk probability cutoff to offer optimal performance for the calculator. This risk calculator was subsequently validated in an external cohort of 1998 patients, where it performed well compared to the inception cohort, with an AUC of 0.81.…”
Section: New Referralsmentioning
confidence: 99%